Effectiveness of edible coatings to inhibit browning and inactivate foodborne pathogens on fresh‐cut apples. Issue 4 (6th April 2020) - Jin, Tony Z.; Chen, Wenxuan; Gurtler, Joshua B.; Fan, Xuetong
Abstract: Multiple formulations of edible coating solutions were developed and evaluated for their ability to maintain the quality and minimize populations of foodborne bacteria on fresh‐cut apples. Fresh‐cut apples were artificially inoculated with Salmonella spp., Escherichia coli O157:H7, and Listeria monocytogenes, and dip‐treated with coating solutions. Changes in populations of pathogens and molds and yeasts (M&Y) were evaluated after solution treatments and during storage at 4°C for 35 days. Changes in color, texture firmness, and weight loss during storage were also determined. Among the formulations, the solution containing 1% of three organic acids (acetic, lactic, and levulinic acids), 2% N‐acetyl‐l‐cysteine or L‐cysteine with 0.5% chitosan demonstrated the best effectiveness for the simultaneous reduction of pathogenic and spoilage microorganisms, control of browning, and maintenance of the quality of fresh‐cut apples. The treated apple slices had nondetectable pathogens and M&Y (<1 log CFU) and the least quality changes for 35‐day storage. The developed solutions can be used at processing plants, retail stores, or homes to protect fresh‐cut apples or other fresh‐cut fruits and vegetables from microbiological and quality deterioration. Abstract : Fresh‐cut apples were dip‐coated in antimicrobial/antibrowning solutions. The developed solutions had the dual effectiveness of both controlling browning and reducing pathogenic bacterial populations, which maintained the fresh‐like appearance and texture of apple slices for 35 days and reduced populations of Salmonella to undetectable levels (<1 log) without growth throughout the storage at 4°C. T1: Control, T2: 1% acids + 2% N‐acetyl‐l‐cysteine; T3: 1% acids + 2% N‐acetyl‐l‐cysteine; T4: 1% acids + 2% L‐cysteine + 0.5% chitosan; T5: 7% calcium ascorbate.